Eksistensi Penglipuran Village Festival IX Sebagai Pengenalan Community Attachment Desa Penglipuran Kabupaten Bangli - Swandewi, Ni Kadek; Swandewi, I Gede; Asmarani, I Gusti Ayu Ratih (Journal of Event and Convention Management, 2023)
Festivals can be interpreted as a celebration by the local community which is part of the arts and performances and includes other activities such as performing music concerts. The 9th Penglipuran Village Festival presents a variety of unique and interesting things, not only limited to performances but more highlighting the socio-cultural wisdom that characterizes the local community. In the Penglipuran Village community, various cultural and ritual events are carried out through a pattern of togetherness or mutual cooperation which involves the entire community including event Penglipuran Village Festival. This research was conducted using observation methods and in-depth interviews with managers event Penglipuran Village Festival which was held for the ninth time. With the theme "Kalpataru" Resurrect The Spirit of Environmental Conservation, This festival aims to introduce traditions and values that grow in society. Through the results of observation and in-depth interviews, it is known that the Penglipuran Village Festival takes values and concepts, as well as full community involvement, making this event have community attachment or sense of belonging. Community attachment make the position of the community as the driving force of events and visitors side by side. The choice of bamboo as the icon for the Penglipuran Village Festival in 2022 can not be separated from what already exists in Penglipuran Village. Community attachment in Penglipuran Village Festival this is associated with the 4S concept, namely Something to see, Something to do, Something to buy, and Something to learn who participated in various activities typical of the local community.